MEANING OF GROWTH anti-environmentalist rhetoric and the defence of modernity. - MCNEILL DOUGLAS, RICHARD (ROUTLEDGE, 2026)
Since the Limits to Growth report was published in 1972 it has been widely known that a commitment to endless growth was putting us on course for environmental disaster-so why have we failed to take decisive political action in the half-century since then? In The Meaning of Growth, Richard McNeill Douglas uses interpretive social science to uncover the cultural roots of political resistance to environmental science and policy.Through a close reading of anti-environmentalist rhetoric the book identifies its idolisation of growth as a defence of a modern (Western-European) world-view, focusing on values of freedom, power, and immortality. The significance of these findings is drawn out by applying the 'secularisation thesis', a theoretical account of the development of a modern understanding of reality from a theological world-view to which it is ostensibly opposed. This framework is used to offer a deep interpretation of what is at stake in environmental debate: that to accept there are limits to growth means abandoning crucial elements of a faith in a theodicy of progress that makes life meaningful in a secular age. Douglas concludes by suggesting that the precondition for political action on the environment is a change of philosophical perspective that provides for a sense of meaning in a world of limits.This book should be of interest to academics in the fields of environmental sociology and communications studies, as well as activists interested in understanding the motivations of anti-environmentalist campaigners and how to counter their influence.
Keywords: Anti-environmentalism.; Economic development -- Environmental aspects.; elektronické knihy; electronic books